1996
DOI: 10.1085/jgp.107.1.79
|View full text |Cite
|
Sign up to set email alerts
|

A slow component of intramembranous charge movement during sarcoplasmic reticulum calcium release in frog cut muscle fibers.

Abstract: Cut muscle fibers from Rana temporaria were mounted in a double Vaseline-gap chamber and equilibrated with an end-pool solution that contained 20 mM EGTA and 1.76 mM Ca (sarcomere length, temperature,[14][15][16] Sarcoplasmic reticulum (SR) Ca release, A[CaT], was estimated from changes in myoplasmic pH (Pape, P.C., D.-S. Jong, and W.K. Chandler. 1995. J. Gen. Physiol. 106:259-336). The maximal value of A[CaT] obtained during a depleting depolarization was assumed to equal the SR Ca content before stimulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
40
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 39 publications
14
40
1
Order By: Relevance
“…Finally, approximation of a single two-state Boltzmann analysis to the charge-voltage curves suggested that RyR antagonists preserved the total charge Q~l,~x despite the kinetic changes. The findings thus parallel results from independent manipulations that altered q~ kinetics but preserved the distinct q~ and q~ transitions with their different properties, their total quantity, and their ON-OFF conservation, when sarcoplasmic reticular Ca 2+ content was depleted (to <10 IxM) or increased (long et al, 1995;Pape et al, 1996; but see also Polakova and Heiny, 1994). Such findings were compatible with an intramembrane qn charge primarily driven by tubular voltage change (Huang and Peachey, 1989;Huang, 1993Huang, , 1994aHuang, , 1994bHui and Chandler 1990).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Finally, approximation of a single two-state Boltzmann analysis to the charge-voltage curves suggested that RyR antagonists preserved the total charge Q~l,~x despite the kinetic changes. The findings thus parallel results from independent manipulations that altered q~ kinetics but preserved the distinct q~ and q~ transitions with their different properties, their total quantity, and their ON-OFF conservation, when sarcoplasmic reticular Ca 2+ content was depleted (to <10 IxM) or increased (long et al, 1995;Pape et al, 1996; but see also Polakova and Heiny, 1994). Such findings were compatible with an intramembrane qn charge primarily driven by tubular voltage change (Huang and Peachey, 1989;Huang, 1993Huang, , 1994aHuang, , 1994bHui and Chandler 1990).…”
Section: Discussionsupporting
confidence: 69%
“…This contrasts with the selective fall in ON charge reported by Garcia et al (1991) that suggested an action of ryanodine mediated solely through its effects on a release of intracellularly stored Ca 2+ that was in turn responsible for driving delayed charge movement. However, it parallels results from independent kinetic manipulations through sarcoplasmic reticular Ca 2+ depletion or loading, which conserved the intramembrane charge 0ong et Pape et al, 1996).…”
Section: Persistence Of On-off Charge Equality In Ryanodine and Daunosupporting
confidence: 63%
See 2 more Smart Citations
“…In particular, the q γ component of the intramembrane charge is thought to represent the electrical signature for conformational transitions in the DHPR-voltage sensor [21,28]. Its steady-state voltage dependence, pharmacological sensitivities particularly to DHPR antagonists [7,20], and its prolonged kinetics near threshold that sharply become more rapid with even slight further depolarization [1,31,38] closely parallel corresponding features of the release of intracellularly stored Ca 2+ [37]. A hypothesis in which such kinetic complexities reflect direct DHPR-RyR interactions would also explain their absence in systems such as cardiac and arthropod skeletal muscle in which a more indirect cellular triggering depends instead upon extracellular Ca 2+ entry [4,15,16,30].…”
Section: Introductionmentioning
confidence: 99%